Microbial diversity in pesticidal and non-pesticidal paddy soil microbiomes - R. SUSANTI; NAINA RIZKI KENARNI; ADI FRANATA JAYA; FARAH FITROTUN NISA’; RISKA LAILA MUKAROMAH; TALITHA WIDIATNINGRUM; NANA KARIADA TRI MARTUTI; MARGARETA RAHAYUNINGSIH (Society for Indonesian Biodiversity, 2023)
Abstract. Susanti R, Kenarni NR, Jaya AF, Nisa’ FF, Mukaromah RL, Widiatningrum T, Martuti NKT, Rahayuningsih M. 2023. Microbial diversity in pesticidal and non-pesticidal paddy soil microbiomes. Biodiversitas 24: 4723-4730. The use of pesticides can affect the physical and chemical properties of paddy soil. Soil physical and chemical properties can indicate soil quality because they affect soil microbial activity. This study used an exploratory observational method to analyze the diversity and abundance of microbes in the soil microbiome of pesticide paddy fields (PPF) and non-pesticide paddy fields (PF). The PPF samples were taken from Purwosari Village, Mijen Subdistrict, Semarang City, while the PF samples were taken from Tambangan Village, Mijen Subdistrict, Semarang City. Soil samples were taken for chemical and metagenomic analysis based on 16S rRNA gene marker region V3-V4. The results showed that microbial PPF diversity was higher than PF's based on the Shannon and Simpson index. The PPF microbiome is dominated by 3 bacterial phyla, namely Proteobacteria (26.61%), Actinobacteriota (15.13%) and Acidobacteriota (11.44%). Meanwhile, the PF microbiome was dominated by Proteobacteria (28.73%), Acidobacteriota (12.80%), and Chloroflexi (11.41%). The Archaea phylum that dominates PPF are Halobacterota (62.78%), Euryarchaeota (20.82%), and Crenarchaeota (10.89%), while in PF it is dominated by Halobacterota (80.43%), Crenarchaeota (11.03%) and Euryarchaeota (5.04%). The phylum that plays an important role in the biodegradation of organochlorine pesticides is Actinobacteria, which dominates in PPF; low abundance of Nitrospirota in PPF as a bioindicator of organochlorine pesticide contamination.